The Functional Resonance Analysis Method as a health care research methodology: a scoping review. Issue 4 (29th April 2022) - McGill, Alexis; Smith, Doug; McCloskey, Rose; Morris, Patricia; Goudreau, Alex; Veitch, Brian
ABSTRACT: Objective: The objective of this review was to examine and map the literature on the use of the Functional Resonance Analysis Method (FRAM) in health care research. Introduction: The FRAM is a resilient health care tool tat offers an approach to deconstruct complex systems by mapping health care processes to identify essential activities, how they are interrelated, and the variability that emerges, which can strengthen or compromise outcomes. Insight into how the FRAM has been operationalized in health care can help researchers and policy-makers understand how this method can be used to strengthen health care systems. Inclusion criteria: This scoping review included research and narrative reports on the application of the FRAM in any health care setting. The focus was to identify the key concepts and definitions used to describe the FRAM; the research questions, aims, and objectives used to study the FRAM; the methods used to operationalize the FRAM; the health care processes examined; and the key findings. Methods: A three-step search strategy was used to find published and unpublished research and narrative reports conducted in any country. Only papers published in English were considered. No limits were placed on the year of publication. CINAHL, MEDLINE, Embase, PsycINFO, Inspec Engineering Village, ProQuest Nursing & Allied Health were searched originally in June 2020 and again in March 2021. A search of the gray literature was also completed in March 2021. Data were extracted from papers by two independent reviewers using a data extraction tool developed by the reviewers. Search results are summarized in a flow diagram, and the extracted data are presented in tabular format. Results: Thirty-one papers were included in the final review, and most (n = 25; 80.6%) provided a description or definition of the FRAM. Only two (n = 2; 6.5%) identified a specific research question. The remaining papers each identified an overall aim or objective in applying the FRAM, the most common being to understand a health care process (n = 20; 64.5%). Eleven different methods of data collection were identified, with interviews being the most common (n = 21; 67.7%). Ten different health care processes were explored, with safety and risk identification (n = 8; 25.8%) being the most examined process. Key findings identified the FRAM as a mapping tool that can identify essential activities or functions of a process (n = 20; 64.5%), how functions are interdependent or coupled (n = 18; 58.1%), the variability that can emerge within a process (n = 20; 64.5%), discrepancies between work as done and work as imagined (n = 20; 64.5%), the resiliency that exists within a process (n = 12; 38.7%), and the points of risk within a process (n = 10, 32.3%). Most papers (n = 27; 87.1%) developed models representing the complexity of a process. Conclusions: The FRAM aims to use a systems approach to examine complex processes and, as evidenced by this review, is suited for use within the health care domain. Interest in the FRAM is growing, with most of the included literature being published since 2017 (n = 24; 77.4%). The FRAM has the potential to provide comprehensive insight into how health care work is done and how that work can become more efficient, safer, and better supported.